A training guide for in situ conservation on- farm (IPGRI, 2000)
This book gives national programmes basic technical skills and tools to build institutional capacity and partnerships to implement an on-farm conservation programme. It discusses the information necessary and the practical steps for the implementation of on-farm conservation, as well as the importance of such an initiative. Equipped with the baseline information from this guide, the reader should then be able to identify and access more detailed information on specialized topics